Question
Answers

The direction ratios of the line $x - y + z - 5 = 0 = x - 3y - 6$are proportional to
$
  {\text{a}}{\text{. }}3,1, - 2 \\
  {\text{b}}{\text{. }}2, - 4,1 \\
  {\text{c}}{\text{. }}\dfrac{3}{{\sqrt {14} }},\dfrac{1}{{\sqrt {14} }},\dfrac{{ - 2}}{{\sqrt {14} }} \\
  {\text{d}}{\text{. }}\dfrac{2}{{\sqrt {41} }},\dfrac{{ - 4}}{{\sqrt {41} }},\dfrac{1}{{\sqrt {41} }} \\
$

Answer Verified Verified
Hint: - Individual multiplication of direction ratios are zero so let’s assume them and write their multiplication with direction vectors of other equation equal to zero.

Let the direction ratios be $l,m,n$
So, in terms of vector it is written as
$\vec a = l\hat i + m\hat j + n\hat k$
Given equations are
$
  x - y + z - 5 = 0 \\
  x - 3y - 6 = 0 \\
$
So, the direction ratios of first equation is $\left( {1, - 1,1} \right)$
So, in terms of vector it is written as
$\vec b = 1\hat i - 1\hat j + 1\hat k$
And the direction ratios of second equation is $\left( {1, - 3,0} \right)$
So, in terms of vector it is written as
$\vec c = 1\hat i - 3\hat j + 0\hat k$
Now, it is a known fact that the direction ratios$l,m,n$is perpendicular to the given equations
Therefore individually multiplication of direction ratios should be zero i.e. its dot product is zero.
i.e. $\vec a.\vec b = 0,{\text{ }}\vec a.\vec c = 0$.

$
   \Rightarrow 1.l - 1.m + 1.n = 0 \\
   \Rightarrow 1.l - 3.m + 0.n = 0 \\
$
Now, solve these two equations
$
  \dfrac{l}{{\left( {\left( { - 1 \times 0} \right) - \left( { - 3 \times 1} \right)} \right)}} = \dfrac{m}{{1 - 0}} = \dfrac{n}{{ - 3 - \left( { - 1} \right)}} \\
  \dfrac{l}{3} = \dfrac{m}{1} = \dfrac{n}{{ - 2}} \\
$
Therefore the direction ratios of the line $x - y + z - 5 = 0 = x - 3y - 6$are proportional to $\left( {3,1, - 2} \right)$
Hence option (a) is correct.

Note: - In such types of questions the key concept we have to remember is that the direction ratios$l,m,n$is always perpendicular to the line equations so, individually multiplication of direction ratios should be zero, i.e. its dot product is zero, then simplify these equations we will get the required answer.

Bookmark added to your notes.
View Notes
×